Computationally efficient approach for simulation of multibody and hydraulic dynamics. (December 2018) - Rahikainen, Jarkko; Kiani, Mehran; Sopanen, Jussi; Jalali, Payman; Mikkola, Aki
Highlights: A monolithic method for simulation of multibody and hydraulic dynamics is proposed. The singular perturbation theory is utilized to increase simulation step size. A case study with implementation details is provided. Increased computational efficiency is achieved. Abstract: A realistic real-time simulation of a complex system, such as an excavator, requires detailed description of the machinery and its components. To take into account the dynamics of entire systems, the model must encompass descriptions of non-mechanical systems, such as hydraulics. For the multibody systems, use of the semi-recursive methods has often been found to be the most efficient solution when the system size increases. For the hydraulic dynamics, in turn, the recently introduced application of the singular perturbation method is a potential candidate for the real-time applications. The main benefit of the application of the singular perturbation method over the conventionally used lumped fluid method is that it overcomes the challenges that the lumped fluid method encounters when numerical stiffness caused by small hydraulic volumes is present in the circuit. Objective of this paper is to improve a recently proposed monolithic formulation for the combined simulation of multibody and hydraulic dynamics via the introduction of the singular perturbation method. Results indicate that the proposed method improves efficiency and robustness when compared to the formulation proposed earlier.